2010
DOI: 10.1016/j.ejcb.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The actin subfamily PtAct4, out of many subfamilies, is differentially localized for specific local functions in Paramecium tetraurelia cells

Abstract: Paramecium tetraurelia possesses more actin isoforms than most other cells. With monospecific antibodies against actin subfamily 4 members, we could label cleavage furrow, nascent food vacuoles, oral apparatus, cilia, cell surface and macronucleus. Expression as green fluorescent protein- (GFP-) fusion protein now allowed us to localize more stringently actin4, e.g., in the macronucleus, particularly when enhanced with anti-GFP antibodies. Posttranscriptional gene silencing of actin4 resulted in disturbances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Of a possible 14 paralogues in these three clades, we injected 11 and were able to detect GFP signal from 7 Rab11-GFP fusion proteins in cells. Subcellular localization patterns were determined in live cells using confocal microscopy and verified both by the highly characteristic morphology of structures, such as the oral apparatus and contractile vacuoles in Paramecium cells (Allen, 2000; Sehring et al , 2010), and colabeling with a subcellular marker dye, LysoTracker (Figure S5 and Supplemental Video S2). The identification of structures by characteristic morphology was conducted using simultaneously captured differential interference contrast images (see Supplemental Video S1 for a representative movie).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Of a possible 14 paralogues in these three clades, we injected 11 and were able to detect GFP signal from 7 Rab11-GFP fusion proteins in cells. Subcellular localization patterns were determined in live cells using confocal microscopy and verified both by the highly characteristic morphology of structures, such as the oral apparatus and contractile vacuoles in Paramecium cells (Allen, 2000; Sehring et al , 2010), and colabeling with a subcellular marker dye, LysoTracker (Figure S5 and Supplemental Video S2). The identification of structures by characteristic morphology was conducted using simultaneously captured differential interference contrast images (see Supplemental Video S1 for a representative movie).…”
Section: Resultsmentioning
confidence: 91%
“…This high number of retained duplicate genes from P. aurelia –specific WGDs (and, possibly, the older WGDs) within the species complex represents a host of candidate intermediates on the path to functional change. There is also evidence that at least some WGD1 paralogues in the P. aurelia complex have diverged in function (Schilde et al , 2010; Sehring et al , 2010; Osin´ska et al , 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Support comes from the facts that ( i ) mechano‐channels are consistently considered associated with the cytoskeleton, notably F‐actin, in other systems (Lapatsina et al, ), this association being mutually interdependent (Kuipers, Middelbeek & van Leeuwen, ); ( ii ) special cortical isoforms, e.g. Pt Act4, have been identified in P. tetraurelia (Sehring et al, ), and ( iii ) subplasmalemmal localisation of actin was shown by immuno‐electron microscopy (Kissmehl et al, ). Therefore, in principle, F‐actin associated with the cell membrane is available for amplifying gravity signals.…”
Section: Graviperception and Gravikinesis/gravitaxismentioning
confidence: 99%
“…Pt Act4 does not only occur in the cortex but is also required for initiating formation of phagosomes and of the cleavage furrow (Sehring et al. ). In Paramecium , para‐/ohnologs evidently may serve for vesicle fusion or budding as well as for cyclosis and to regulate access of vesicles to other membranes.…”
Section: Specific Conservation and Changes During Evolutionmentioning
confidence: 99%
“…Importantly, localization differs for the different actin paralogs of Paramecium (Sehring et al. , ). It may also indicate different binding to other proteins and different polymerization kinetics—predictions to be scrutinized.…”
Section: Specific Conservation and Changes During Evolutionmentioning
confidence: 99%